2023
DOI: 10.1186/s12877-023-04403-1
|View full text |Cite
|
Sign up to set email alerts
|

The stroke transitional care intervention for older adults with stroke and multimorbidity: a multisite pragmatic randomized controlled trial

Maureen Markle-Reid,
Kathryn Fisher,
Kimberly M. Walker
et al.

Abstract: Background This study aimed to test, in real-world clinical practice, the effectiveness of a Transitional Care Stroke Intervention (TCSI) compared to usual care on health outcomes, self-management, patient experience, and health and social service use costs in older adults (≥ 55 years) with stroke and multimorbidity (≥ 2 chronic conditions). Methods This pragmatic randomized controlled trial (RCT) included older adults discharged from hospital to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…Regarding the impact on depression for stroke survivors, two interventions (an educational website with remote monitoring 37 and an information website combined with monthly follow-up with a nurse 39 ) significantly reduced anxiety or depressive symptoms for stroke survivors ( P < 0.001 and P = 0.008, respectively), while the three other did not. 36 , 40 , 41 Another study found that increased mastery and social support gained using a website were significantly correlated with reduced depression of stroke survivors (respectively r = −0.49: P < 0.005, and r = −0.37; P < 0.05) at one month. 42 In addition, the qualitative study reported by Smith et al 44 characterized the process of emotional adjustment after stroke and the role of the online forum in this process.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Regarding the impact on depression for stroke survivors, two interventions (an educational website with remote monitoring 37 and an information website combined with monthly follow-up with a nurse 39 ) significantly reduced anxiety or depressive symptoms for stroke survivors ( P < 0.001 and P = 0.008, respectively), while the three other did not. 36 , 40 , 41 Another study found that increased mastery and social support gained using a website were significantly correlated with reduced depression of stroke survivors (respectively r = −0.49: P < 0.005, and r = −0.37; P < 0.05) at one month. 42 In addition, the qualitative study reported by Smith et al 44 characterized the process of emotional adjustment after stroke and the role of the online forum in this process.…”
Section: Resultsmentioning
confidence: 96%
“…Six online resources combined access to a website and additional support from a professional: the Michigan Stroke Transition Trial (MISTT) (Strong et al 34 and Reeves et al 35 ) combined access to the MISTT website with home visit and telephone-based case management; the RESCUE website (Lelaurin et al 36 ), was combined with a nurse follow-up; the STROKE-CARD (Willeit et al 37 ) combined access to an educational website with remote monitoring and an appointment with a multidisciplinary team; the TEMpEST website (Demir Avci and Gözüm 38 ) combined access to a website with nurses and coordinator follow-up and home visits; the Virtual Multidisciplinary Stroke Care Clinic (VMSCC) (Lo et al 39 ) combined a website with video-based consultation and telephone calls with a nurse; and the Transitional Care Stroke Intervention (TCSI) (Markle-Reid et al 40 ) combined access to the My Stroke Recovery Journey website with a coordinator and interprofessional team follow-up. Two studies used only a website without additional professional support: the Caring∼Web© (Pierce et al 41 ) website and the resource evaluated by Smith et al 42 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations